Treatment of stress urinary incontinence using polyacrylamide hydrogel in women after radiotherapy: 1-year follow-up - Krhut, Jan; Martan, Alois; Juráková, Michaela; Němec, David; Mašata, Jaromír; Zvara, Peter (International urogynecology journal, 2016)
INTRODUCTION AND HYPOTHESIS: Information on urethral bulking therapy in women after previous pelvic radiotherapy is lacking. This study compared the safety and efficacy of polyacrylamide intraurethral injections in patients with and without previous radiotherapy. METHODS: A total of 46 patients with severe stress urinary incontinence (SUI) were enrolled in this multicenter prospective trial. Group A consisted of 24 patients with previous radiotherapy to the pelvis for the treatment of a gynaecological malignancy. Group B consisted of 22 patients without previous radiotherapy. All patients were treated with a transurethral injection of a bulking solution (Bulkamid). The average follow-up was 12.4 months. The paired Wilcoxon test was used to compare the results before and after the procedure within the groups, and the two-sample Wilcoxon test was used for comparisons between groups. RESULTS: Complete continence was achieved in 25 % of patients in group A and in 36.4 % of patients in group B. Significantly reduced urine leakage was observed in both groups (p = 0.0164 in group A and p = 0.0002 in group B). The total scores in the International Consultation on Incontinence Questionnaire decreased by 5.2 in group A (p = 0.0000) and 6.36 in group B (p = 0.0001). The scores for the Total Patient Perception of Bladder Condition decreased by 1.54 in group A (p = 0.0001) and 2.59 in group B (p = 0.0000), with a significant difference between groups (p = 0.0224). No clinically significant changes in urodynamic parameters were observed. No severe adverse events were noted. CONCLUSIONS: Based on our results, we conclude that urethral bulking therapy is a valuable treatment option in patients with severe SUI who have undergone pelvic radiotherapy for the treatment of gynaecological malignancy.
Keywords: senioři; senioři nad 80 let; výsledek terapie; Biocompatible Materials; Surveys and Questionnaires; Female; Humans; Acrylic Resins; akrylové pryskyřice; lidé; Prospective Studies; stresová inkontinence moči; Middle Aged; ženské pohlaví; lidé středního věku; Urinary Incontinence, Stress; nádory ženských pohlavních orgánů; průzkumy a dotazníky; Aged, 80 and over; Hydrogels; Treatment Outcome; prospektivní studie; hydrogely; dospělí; Adult; Genital Neoplasms, Female; Aged; biokompatibilní materiály